Transformasi Edupreneurship: Studi Empiris Program Mahasiswa Wirausaha Terhadap Minat Berwirausaha Mahasiswa Pendidikan Ekonomi Universitas Sriwijaya - Jaenudin, Riswan; Priti, Priti (Universitas Hamzanwadi, 2025)
This research proves the influence of edupreneurship based on the Student Entrepreneurship Program (PMW) on the entrepreneurial interest of Sriwijaya University Economics Education Study Program students. The method used is quantitative with an associative approach. The research sample consisted of 51 students who received PMW funding in 2023 and 2024. Data collection techniques through questionnaires, interviews, and documentation. Data analysis uses prerequisite tests, namely normality and linearity tests of simple regression; and hypothesis testing includes Pearson product moment correlation, coefficient of determination, and t-test. The results showed that PMW-based edupreneurship affects entrepreneurial interest with a correlation of 0.475 (medium). The coefficient of determination shows an influence of 22.63 percent, while the rest is influenced by other factors such as family environment and self-confidence. The t-test shows that tcount = 3.78 is greater than ttable = 2.009, so the hypothesis is accepted, which means that there is an effect of edupreneurship based on the Student Entrepreneurship Program (PMW) on the entrepreneurial interest of students of the Economic Education Study Program of Sriwijaya University.